Exploring English for pharmacy: A systematic literature review of pedagogical trends and challenges - Dewi, Kadek Maya Cyntia; Santosa, Made Hery (Indonesian Research Journal in Education |IRJE|, 2025)
Effective English for Specific Purposes (ESP) programs adapted to pharmacy education are necessary, as evidenced by the growing importance of English in the worldwide pharmaceutical business. The pedagogical trends, difficulties, and best practices in teaching English for pharmacy during the past ten years (2014–2024) are examined in this comprehensive literature review. The review reveals significant topics by examining 14 studies from international databases, including curriculum development, pedagogical innovations, student perspectives, and English usage and needs analysis. The results indicate significant deficiencies in pharmacy professionals’ technical vocabulary, oral communication, and scientific writing abilities, which impede their success in school and the workplace. This study aims to improve pharmacy graduates' communication skills in a field that is becoming increasingly globalized by serving as a roadmap for future research and curriculum design.